(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
The current research aims to shed light on the theoretical and practical foundations of the green value stream mapping technology by building a model that presents the technical and knowledge foundations for the purpose of assisting economic units in reducing the rates of environmental pollution occurring and areas of cost reduction and improving the quality of services to reach sustainable performance, in addition to clarifying the role of Green value stream map technology in the optimal utilization of resources and energy, reduce costs and improve the quality of services. Furthermore, determining the extent of compatibility between the green value stream map technology and the financial and non-financial indicators of the performance card to achieve sustainable performance of service units. Evaluation and measurement of sustainable performance helps the university in good strategic management and enables it to formulating, following up, and evaluating its strategies in a more organized manner. Moreover, presenting a model of green value stream mapping technology to enhance sustainable performance in educational institutions highlighting the role of green value stream mapping technology in optimal utilization of resources and productive capacities and low service costs to achieve sustainable performance in economic units, including universities for the purpose of sustainable educational services. In order to achieve the objectives of the research, the analytical quantitative approach was relied on to study the case at Al-Qasim Green University and the financial and non-financial data (2018-2019) to present and analyze the costs and then re-measure the costs of the educational service according to the green value stream map and the reflection of its results on sustainable performance of Al-Qasim Green University, which includes sustainable financial and non-financial indicators. One of the most important conclusions reached by the research is that there is a possibility to measure sustainable performance in educational institutions in a varying manner between the approved indicators. Additionally, the use of the green value stream map has a positive role in increasing the level of sustainable performance as it is an effective method to reduce costs and reduce losses as it helps in identifying energies and comparing the current and future value stream map.